2018
DOI: 10.1016/j.bbamem.2018.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis signal regulating kinase-1 and NADPH oxidase mediate human amylin evoked redox stress and apoptosis in pancreatic beta-cells

Abstract: Misfolded toxic human islet amyloid polypeptide or amylin (hA) and plasma membrane-associated redox complex, NADPH oxidase (NOX), have been implicated in the islet β-cell demise associated with type-2 diabetes mellitus (T2DM). Studies show that hA accumulation is stressful to β-cells and that misfolding of human amylin evokes redox stress and activates mitogen activated protein (MAP) kinases, p38 MAPK and c-Jun N-terminal (JNK) kinase. However, the molecular link and causality between hA-evoked redox stress, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 68 publications
(102 reference statements)
0
20
0
Order By: Relevance
“…Previous studies indicated that either exposure of beta cells to hA or hA-overexpression in cells results in intracellular ROS accumulation, supporting the hypothesis that hA aggregation might be a cause of oxidative stress [94], possibly through mitochondrial dysfunction [95]. Recent work identified that a misfolded amylin actually activates an upstream apoptosis signal regulating kinase-1 (ASK1), with a concomitant decrease in the intracellular levels of reduced glutathione [96]. Moreover, the pro-oxidative activity and expression of a plasma membrane bound NADPH oxidase (NOX) and its regulatory subunits were stimulated, suggesting that NOX1 and ASK1 mediate the cytotoxic effect of aggregated hA in pancreatic beta-cells [96].…”
Section: Aggregation Can In Turn Produce Oxidative Stress or Prmentioning
confidence: 90%
See 3 more Smart Citations
“…Previous studies indicated that either exposure of beta cells to hA or hA-overexpression in cells results in intracellular ROS accumulation, supporting the hypothesis that hA aggregation might be a cause of oxidative stress [94], possibly through mitochondrial dysfunction [95]. Recent work identified that a misfolded amylin actually activates an upstream apoptosis signal regulating kinase-1 (ASK1), with a concomitant decrease in the intracellular levels of reduced glutathione [96]. Moreover, the pro-oxidative activity and expression of a plasma membrane bound NADPH oxidase (NOX) and its regulatory subunits were stimulated, suggesting that NOX1 and ASK1 mediate the cytotoxic effect of aggregated hA in pancreatic beta-cells [96].…”
Section: Aggregation Can In Turn Produce Oxidative Stress or Prmentioning
confidence: 90%
“…Human Amylin (hA) is a 4 kDa pancreatic hormone, synthesized and secreted along with insulin by islet beta cells. Like other amyloid proteins, it is prone to aggregation and remains a hallmark of type-2 diabetes mellitus [96]. Previous studies indicated that either exposure of beta cells to hA or hA-overexpression in cells results in intracellular ROS accumulation, supporting the hypothesis that hA aggregation might be a cause of oxidative stress [94], possibly through mitochondrial dysfunction [95].…”
Section: Aggregation Can In Turn Produce Oxidative Stress or Prmentioning
confidence: 99%
See 2 more Smart Citations
“…Glycogen accumulation upon hyperglycemia is also setting conditions for apoptosis (40). In progressed diabetic states, amyloid polypeptide and NOXs are activated by the MAPK-JNK pathway when amyloid polypeptide activates apoptosis via the apoptosis signal-regulating kinase-1 (ASK1) (75, 102, 258).…”
Section: Oxidative Stress and Antioxidant Protection In Pancreatic β-mentioning
confidence: 99%